Anatomic patterns and clinical significance of gastrocolic trunk of Henlé in laparoscopic right colectomy for colon cancer: Results of the HeLaRC trial. (August 2022) - He, Zirui; Yang, Chunkang; Diao, Dechang; Wu, Deqing; Fingerhut, Abe; Sun, Yueming; Gao, Yuan; Wang, Nan; Li, Ang; Tong, Weidong; Ding, Peirong; Xiao, Yi; et al.
Abstract: Background: Recent interest in laparoscopic right colectomy with D3 lymphadenectomy for right colon cancer, has raised renewed attention to the anatomic variations of the gastrocolic trunk of Henlé (GTH). Understanding the vascular structure of the GTH region for individual patients should improve surgical outcomes. The goal of this nationwide multicenter study (Anatomical Classification of Henlé's Trunk in Laparoscopic Right Hemi-colectomy (HeLaRC) trial) was to study the anatomic patterns of the GTH region, to clarify the implications of GTH in laparoscopic right colectomy with D3 lymphadenectomy (D3-RC) and analyze their clinical significance. Methods: We enrolled 583 patients from 26 centers across China who underwent D3-RC. The number of tributaries, length and types of GTH constitutions and their influence on intra-operative data were investigated. A nomogram score (based on the length of GTH, body mass index (BMI), tumor location, T stage and type of GTH (type I vs. non-type I) was established to assess the potential hazard of bleeding. Results: The GTH was found in 567 patients (97.3%). The distribution of GTH types was 0 (14.1%, n = 80), I (53.3%, n = 302), II (27.0%, n = 153), III (5.6%, n = 32). Of note, the type I GTH, T1 stage and tumor location at ileocecal or ascending colon were correlated with shorter exposure time of the GTH region ( P < 0.0001). Short length of GTH ( P = 0.002) and tumor location (transverse colon vs. non transverse colon) ( P = 0.003) were correlated with the amount of GTH bleeding during the surgery. Nomogram discrimination was good (C-index: 0.72 (95% CI: 0.64, 0.80)). The dissection plane was better in patients with type I GTH than with other types ( P = 0.023). Conclusion: GTH pattern variations may affect surgical outcomes in patients undergoing D3-RC. Better recognition of GTH anatomy might lead to a safer operation with better oncologic quality. Highlights: The first nationwide multicenter study on the anatomy of gastrocolic trunk of Henlé (GTH) and its clinical significance. Better recognition of GTH composition and spatial orientation could lead to a safer operation with better oncologic quality in patients undergoing laparoscopic right colectomy with D3 lymphadenectomy.